Application of power spectra patterns in Fourier transform square wave voltammetry to evaluate electrode kinetics of surface-confined proteins. - Fleming, B; Barlow, N; Zhang, J; Bond, A; Armstrong, F (2006)
This paper describes an application of Fourier transform (FT) voltammetry that provides a quantitative evaluation of the electron-transfer kinetics of protein molecules attached to electrode surfaces. The potential waveform applied in these experiments consists of a large-amplitude square wave of frequency f superimposed onto the traditional triangular voltage used in dc cyclic voltammetry. The resultant current-time response, when Fourier transformed into the frequency domain, provides patterns of data at the even harmonic frequencies that arise from nonlinearity in the Faradaic response. These even harmonic contributions are ideally suited for kinetic evaluation of electron-transfer processes because they are highly selective to quasi-reversible behavior (insensitive to reversible or irreversible processes) and almost devoid of background charging current. Inverse FT methods can then be used to provide the wave shapes of the dc as well as the ac voltammetric components and other characteristics employed to detect the level of nonideality present relative to theoretical models based upon noninteracting surface-confined molecules. The new form of data evaluation has been applied to the electron-transfer properties of a typical biological electron carrier, the blue copper protein azurin, immobilized on polycrystalline gold electrodes modified with self-assembled monolayers of different length alkanethiols. Details of the electrode kinetics (rates of electron transfer, dispersion, and charge-transfer coefficients) as a function of alkanethiol, apparent surface coverage, and capacitance are all deduced from the square wave (FT-inverse FT) protocol, and the implications of these findings are considered.